Aqueous ink for inkjet recording

The water-based ink for inkjet recording, formulated with specific polyurethane and acrylic polymer components, addresses the challenges of adhesion and friction resistance on polyolefin films while being environmentally friendly, surpassing the limitations of existing inks.

JP2025047711AActive Publication Date: 2025-04-03DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023156370
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-21
Publication Date
2025-04-03
Estimated Expiration
2043-09-21

AI Technical Summary

Technical Problem

Existing water-based inks for inkjet recording struggle to achieve excellent durability, such as adhesion and friction resistance, on polyolefin plastic films, and they are not environmentally friendly due to the use of petroleum-derived materials.

Method used

A water-based ink for inkjet recording is developed, comprising water, a water-soluble organic solvent, pigment, surfactant, wax, polyurethane resin, and acrylic polymer. The polyurethane resin is derived from a five-membered cyclic carbonate compound and a diamine compound, and the acrylic polymer is an A-B block copolymer, with specific molecular weight and acid value ranges, to enhance adhesion and friction resistance.

Benefits of technology

The ink achieves excellent adhesion and friction resistance on polyolefin plastic films, while being environmentally friendly due to the use of carbon dioxide-derived materials and plant-based methacrylates, thus addressing the limitations of existing inks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025047711000001
    Figure 2025047711000001
  • Figure 2025047711000002
    Figure 2025047711000002
  • Figure 2025047711000003
    Figure 2025047711000003
Patent Text Reader

Abstract

To provide aqueous ink for inkjet recording that enables recording of an image of a printing film excellent in adhesion and durability such as friction resistance to a printing base material such as a polyolefin-based plastic film, and to which an environment consideration type technique is applied.SOLUTION: Aqueous ink for inkjet recording contains water, a water-soluble organic solvent, a pigment, a surface active agent, a wax, a polyurethane resin, and an acrylic polymer, wherein the polyurethane resin is a polyhydroxy polyurethane resin having a constitutional unit derived from a five-membered cyclic carbonate compound which is a reaction product of a diepoxy compound and carbon dioxide, and a constitutional unit derived from a diamine compound, the acrylic polymer is an A-B block copolymer having an A chain and a B chain, and a content of the polyhydroxy polyurethane resin with respect to 100 pts.mass of the A-B block copolymer is 1 to 100 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-based ink for ink-jet recording. [Background technology]

[0002] Due to its high functionality, the inkjet printing method is widely used for personal use, office use, business use, recording, color display, and color photography. In recent years, the range of application has expanded from consumer inkjet printers for offices and wide-format inkjet printers for large-format printing to inkjet printers, which are industrial equipment. Since the inkjet printing method does not require printing plates, it is useful as a method for obtaining small quantities of various industrial printed materials on demand. In addition, from the viewpoint of environmental consideration, inkjet printing methods using aqueous inks have been actively proposed.

[0003] Industrial applications include, for example, sign displays, outdoor advertising, facility signs, displays, POP advertising, transportation advertising, packaging, containers, and labels. Printing substrates (recording media) applicable to these applications include paper media such as paper, cardboard, photo paper, and inkjet paper; plastic media such as polyvinyl chloride, polyolefin, polyester, and nylon; and fabrics such as cotton cloth, ester cloth, nylon fabric, and nonwoven fabric. Furthermore, for industrial applications, on-demand printing that does not require a plate is mainstream, and high-speed printing suitability is required. And, since images recorded with aqueous inks containing dyes as coloring materials are poor in durability such as water resistance and light resistance, aqueous inks containing pigments as coloring materials are used.

[0004] In order to record images with improved durability, inkjet inks have been proposed that contain acrylic or urethane binder components capable of forming a film (Patent Documents 1 and 2). In the case of aqueous inks for inkjet recording that contain a pigment as a coloring material, the pigment must be stably finely dispersed. For example, a pigment dispersion in which a pigment is stably finely dispersed over time using a surfactant or polymer dispersant, and an inkjet ink using this have been proposed (Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4157868 [Patent Document 2] Special Publication No. 2009-515007 [Patent Document 3] International Publication No. 2013 / 008691 Summary of the Invention [Problem to be solved by the invention]

[0006] However, even with the inkjet inks proposed in Patent Documents 1 to 3, it was difficult to record images with excellent adhesion and durability such as abrasion resistance on a printing substrate such as a polyolefin-based plastic film.

[0007] Meanwhile, in view of the recent trend of global warming, the problem of carbon dioxide emissions, resource problems, and marine plastic problems, the importance of environmentally friendly technology is increasing. As the binder resin and polymer dispersant for dispersing the pigment blended in conventional water-based inks and water-based pigment dispersions, resins and the like synthesized using raw materials such as monomers derived from petroleum materials are used. In other words, images recorded with conventional water-based inks are mainly formed from materials derived from petroleum materials, and it cannot be said that environmentally friendly technology is necessarily applied.

[0008] In the past, inkjet printing technology was used for printing substrates such as containers and labels made of biodegradable plastics such as polylactic acid and polyhydroxyalkanoic acid. However, there was a problem in that environmentally friendly technology was not necessarily applied sufficiently to images recorded on such printing substrates.

[0009] The present invention has been made in consideration of the problems associated with the conventional techniques, and an object of the present invention is to provide a water-based ink for inkjet recording that employs an environmentally friendly technology and that is capable of recording images such as printed films that have excellent adhesion and durability such as abrasion resistance on printing substrates such as polyolefin-based plastic films. [Means for solving the problem]

[0010] That is, according to the present invention, there is provided the following water-based ink for ink-jet recording. [1] A water-based ink for inkjet recording, comprising water, a water-soluble organic solvent, a pigment, a surfactant, a wax, a polyurethane resin, and an acrylic polymer, wherein the polyurethane resin is a polyhydroxy polyurethane resin having a constituent unit derived from a five-membered cyclic carbonate compound that is a reaction product of a diepoxy compound and carbon dioxide, and a constituent unit derived from a diamine compound, the acrylic polymer is an AB block copolymer having an A chain and a B chain, and the content of the polyhydroxy polyurethane resin per 100 parts by mass of the AB block copolymer is 1 to 100 parts by mass. [2] The aqueous ink according to [1], wherein the polyhydroxy polyurethane resin has a weight average molecular weight of 10,000 to 100,000, a hydroxyl value of 150 to 250 mg KOH / g, and an acid value of 20 to 50 mg KOH / g, and the polyhydroxy polyurethane resin is contained in the form of particles having a number average particle diameter of 20 to 300 nm. [3] The aqueous ink according to [1] or [2], wherein the AB block copolymer satisfies the following requirements (1) to (3): (1) Contains 90% by mass or more of structural units derived from methacrylic acid and methacrylate monomers, The number average molecular weight is 10,000 to 60,000, the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.8 or less, and the acid value is 20 to 100 mgKOH / g. (2) The A chain has a structural unit (A) derived from at least one methacrylate monomer selected from the group consisting of methyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, ethyl methacrylate, isobornyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, behenyl methacrylate, and tetrahydrofurfuryl methacrylate; The content of the structural unit (A) in the A chain is 80 mass% or more, and the A chain has a glass transition temperature of 150°C or less, a number average molecular weight of 3,000 to 50,000, and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.8 or less. (3) The B chain has a structural unit (B-1) derived from methacrylic acid, and a structural unit (B-2) derived from at least one methacrylate monomer selected from the group consisting of methyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, ethyl methacrylate, isobornyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, behenyl methacrylate, and tetrahydrofurfuryl methacrylate, in the B chain, the content of the structural unit (B-2) is 80 mass% or more based on the total content of structural units other than the structural unit (B-1), The acid value of the B chain is 50 to 250 mgKOH / g and the number average molecular weight is 1,000 to 11,000, At least a portion of the carboxy groups in the B chain is neutralized with an alkali. [4] The aqueous ink according to [3], wherein the alkali is at least one selected from the group consisting of ammonia, dimethylaminoethanol, 2-amino-1-propanol, sodium hydroxide, potassium hydroxide, lithium hydroxide, linear aliphatic amines having 6 to 22 carbon atoms, branched aliphatic amines having 6 to 22 carbon atoms, and unsaturated aliphatic amines having 6 to 22 carbon atoms. [5] The aqueous ink according to any one of [1] to [4], wherein the surfactant is at least one selected from the group consisting of silicone-based surfactants, acetylene glycol-based surfactants, and fluorine-based surfactants. [6] The water-based ink according to any one of [1] to [5] above, wherein the wax is a polyethylene wax. [7] The aqueous ink according to any one of [1] to [6], wherein the water-soluble organic solvent comprises propylene glycol and at least one selected from the group consisting of diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and dipropylene glycol monomethyl ether, and the content of the water-soluble organic solvent is 3 to 30 mass% based on the total mass of the ink. Effect of the Invention

[0011] According to the present invention, it is possible to provide a water-based ink for inkjet recording that employs environmentally friendly technology and that is capable of recording images such as printed films that have excellent adhesion and durability such as abrasion resistance on printing substrates such as polyolefin-based plastic films. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] <Water-based ink> Hereinafter, the embodiment of the present invention will be described, but the present invention is not limited to the following embodiment. One embodiment of the aqueous ink of the present invention is an aqueous ink for inkjet recording containing water, a water-soluble organic solvent, a pigment, a surfactant, a wax, a polyurethane resin, and an acrylic polymer. The polyurethane resin is a polyhydroxy polyurethane resin having a constitutional unit derived from a 5-membered ring cyclic carbonate compound which is a reaction product of a diepoxy compound and carbon dioxide, and a constitutional unit derived from a diamine compound. The acrylic polymer is an AB block copolymer having an A chain and a B chain. In the aqueous ink, the content of the polyhydroxy polyurethane resin is 1 to 100 parts by mass relative to 100 parts by mass of the AB block copolymer. Hereinafter, the aqueous ink of this embodiment will be described in detail.

[0013] (Polyhydroxypolyurethane resin) The polyhydroxy polyurethane resin has a constitutional unit derived from a 5-membered cyclic carbonate compound and a constitutional unit derived from a diamine compound. The polyhydroxy polyurethane resin has a structure represented by the following general formula (1), for example. The polyhydroxy polyurethane resin has a large number of hydroxyl groups (OH groups) in the molecular chain. When such a polyhydroxy polyurethane resin is contained in an aqueous ink, it is considered that an image can be formed that is a printed film having excellent adhesion to polyolefin-based plastic films and the like, since the hydroxyl groups are hydrophilic.

[0014] TIFF2025047711000001.tif27170

[0015] As shown in the following reaction formula (A), the five-membered ring cyclic carbonate compound represented by general formula (3) is a reaction product obtained by reacting the diepoxy compound represented by general formula (2) with carbon dioxide. The five-membered ring cyclic carbonate compound can be obtained, for example, by reacting the diepoxy compound with carbon dioxide for 10 to 20 hours in the presence or absence of an organic solvent, at a temperature of 40 to 150°C, at normal pressure or slightly pressurized conditions, and in the presence of a catalyst.

[0016] TIFF2025047711000002.tif37170[References] ·N.Kihara,T.Endo,J.Org.Chem.,1993,58,6198 ·N.Kihara,T.Endo,J.Polymer Sci.,PartA Polmer Chem.,1993,31(12),2765

[0017] As the diepoxy compound, for example, any of the compounds represented by the following formulas (2-1) to (2-18) as well as commercially available compounds having two epoxy groups in the molecule can be used.

[0018] TIFF2025047711000003.tif226170

[0019] TIFF2025047711000004.tif255165

[0020] Examples of the catalyst used in the reaction of the diepoxy compound with carbon dioxide include base catalysts and Lewis acid catalysts. Examples of the base catalyst include tertiary amines such as triethylamine, tributylamine, diazabicycloundecene, diazabicyclooctane, and pyridine; alkali metal salts such as lithium chloride, lithium bromide, lithium fluoride, and sodium chloride; alkaline earth metal salts such as calcium chloride; quaternary ammonium salts such as tetrabutylammonium chloride, tetraethylammonium bromide, and benzyltrimethylammonium chloride; carbonates such as potassium carbonate and sodium carbonate; metal acetates such as zinc acetate, lead acetate, copper acetate, and iron acetate; metal oxides such as calcium oxide, magnesium oxide, and zinc oxide; phosphonium salts such as tetrabutylphosphonium chloride; and the like.

[0021] Lewis acid catalysts include tin compounds such as tetrabutyltin, dibutyltin dilaurate, dibutyltin diacetate, and dibutyltin octoate.

[0022] The amount of catalyst is preferably 0.1 to 50 parts by mass, more preferably 0.3 to 20 parts by mass, per 50 parts by mass of diepoxy compound. If the amount of catalyst is too small, the effect of the catalyst may be insufficient. On the other hand, if the amount of catalyst is too large, the performance of the finally obtained polyhydroxy polyurethane resin may be easily deteriorated.

[0023] Examples of organic solvents that can be used during the reaction of a diepoxy compound with carbon dioxide include dimethylformamide, dimethylsulfoxide, dimethylacetamide, N-methylpyrrolidone, N-ethylpyrrolidone, and tetrahydrofuran. These organic solvents may also be used in combination with other poor solvents. Examples of other poor solvents include methyl ethyl ketone, xylene, toluene, tetrahydrofuran, diethyl ether, and cyclohexanone.

[0024] As shown in the following reaction formula (B), the polyhydroxy polyurethane resin represented by general formula (1) can be obtained by reacting a five-membered cyclic carbonate compound represented by general formula (3) with a diamine compound represented by general formula (4) in the presence of an organic solvent at a temperature of 20 to 150°C.

[0025] TIFF2025047711000005.tif66170

[0026] As the diamine compound, any of the known diamine compounds used in producing polyurethane resins can be used. As the diamine compound, for example, aliphatic diamines such as methylenediamine, ethylenediamine, trimethylenediamine, 1,3-diaminopropane, hexamethylenediamine, and octamethylenediamine; aromatic diamines such as phenylenediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane, 4,4'-methylenebis(phenylamine), 4,4'-diaminodiphenylether, 4,4'-diaminodiphenylsulfone, metaxylylenediamine, and paraxylylenediamine; alicyclic diamines such as 1,4-cyclohexanediamine, 4,4'-diaminocyclohexylmethane, 1,4'-diaminomethylcyclohexane, and isophoronediamine; alkanol diamines such as monoethanoldiamine, ethylaminoethanolamine, and hydroxyethylaminopropylamine; and the like can be mentioned.

[0027] The polyhydroxy polyurethane resin is preferably contained in the aqueous ink in the form of particles. That is, the aqueous ink preferably contains resin particles formed of the polyhydroxy polyurethane resin. The resin particles formed of the polyhydroxy polyurethane resin can be dispersed in the aqueous ink by a conventional method. For example, the resin particles can be dispersed in the aqueous ink or the aqueous medium used for the aqueous ink by adding and neutralizing a carboxy group to the polyhydroxy polyurethane resin. More specifically, maleic anhydride is added to the polymerization solution obtained by polymerizing the polyhydroxy polyurethane resin while stirring, thereby adding a carboxy group to the polyhydroxy polyurethane resin. Next, alkaline water is added to neutralize the added carboxy group, thereby dispersing the resin particles formed of the polyhydroxy polyurethane resin in the aqueous medium.

[0028] The weight average molecular weight (Mw) of the polyhydroxy polyurethane resin is preferably 10,000 to 100,000. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the resin or polymer in this specification are values ​​calculated as polystyrene measured by gel permeation chromatography (GPC). If the weight average molecular weight of the polyhydroxy polyurethane resin is less than 10,000, the strength of the printed film formed may be slightly reduced. On the other hand, if the weight average molecular weight of the polyhydroxy polyurethane resin is more than 100,000, problems such as excessive increase in the particle size of the resin particles may easily occur.

[0029] The hydroxyl value of the polyhydroxy polyurethane resin is preferably 150 to 250 mgKOH / g. If the hydroxyl value of the polyhydroxy polyurethane resin is less than 150 mgKOH / g, the carbon dioxide reduction effect may be somewhat insufficient. On the other hand, if the hydroxyl value of the polyhydroxy polyurethane resin is more than 250 mgKOH / g, the physical properties of the polyhydroxy polyurethane resin as a polymer may be somewhat insufficient.

[0030] The acid value of the polyhydroxy polyurethane resin is preferably 20 to 50 mgKOH / g. If the acid value of the polyhydroxy polyurethane resin is less than 20 mgKOH / g, problems such as excessive increase in particle size of the resin particles may occur. On the other hand, if the acid value of the polyhydroxy polyurethane resin is more than 50 mgKOH / g, the water resistance and chemical resistance of the formed printing film may be slightly decreased.

[0031] When the polyhydroxy polyurethane resin is contained in the aqueous ink in the form of resin particles, the number average particle diameter of the resin particles is preferably 20 to 300 nm. If the number average particle diameter of the resin particles is less than 20 nm, the strength of the printed film formed may be slightly decreased. On the other hand, if the number average particle diameter of the resin particles is more than 300 nm, the ejection property from the nozzle of the inkjet recording head may be slightly decreased.

[0032] (AB block copolymer) The aqueous ink of this embodiment contains an acrylic polymer that is an AB block copolymer having an A chain and a B chain. The AB block copolymer (acrylic polymer) and the above-mentioned polyhydroxy polyurethane resin (polyurethane resin) are both components that function as binders for the ink. By using the AB block copolymer and the polyhydroxy polyurethane resin in combination, an image that is a printing film with excellent durability can be formed.

[0033] In the aqueous ink, the content of the polyhydroxy polyurethane resin relative to 100 parts by mass of the AB block copolymer is preferably 1 to 100 parts by mass, more preferably 10 to 50 parts by mass. If the content of the polyhydroxy polyurethane resin is too low, the durability of the printed film formed decreases. On the other hand, if the content of the polyhydroxy polyurethane resin is too high, the storage stability of the ink decreases.

[0034] In the aqueous ink, the content of the binder (solid content) relative to 100 parts by mass of the pigment is preferably 50 to 505 parts by mass, and more preferably 100 to 400 parts by mass. The binder (solid content) is the total of the polyhydroxy polyurethane resin and the AB block copolymer. If the content of the binder relative to 100 parts by mass of the pigment is less than 50 parts by mass, the adhesion of the formed print film to the plastic film and the abrasion resistance may be somewhat insufficient. On the other hand, if the content of the binder relative to 100 parts by mass of the pigment is more than 505 parts by mass, the pigment concentration is relatively decreased, and the color development of the image may be somewhat decreased.

[0035] The AB block copolymer preferably satisfies the following requirements (1) to (3).

[0036] (1) Contains 90% by mass or more of structural units derived from methacrylic acid and methacrylate monomers, The number average molecular weight is 10,000 to 60,000, the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.8 or less, and the acid value is 20 to 100 mgKOH / g.

[0037] (2) The A chain has a structural unit (A) derived from at least one methacrylate monomer selected from the group consisting of methyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, ethyl methacrylate, isobornyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, behenyl methacrylate, and tetrahydrofurfuryl methacrylate; The content of the structural unit (A) in the A chain is 80 mass% or more, and the A chain has a glass transition temperature of 150°C or less, a number average molecular weight of 3,000 to 50,000, and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.8 or less.

[0038] (3) the B chain has a structural unit (B-1) derived from methacrylic acid, and a structural unit (B-2) derived from at least one methacrylate monomer selected from the group consisting of methyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, ethyl methacrylate, isobornyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, behenyl methacrylate, and tetrahydrofurfuryl methacrylate; in the B chain, the content of the structural unit (B-2) is 80 mass% or more based on the total content of structural units other than the structural unit (B-1), The acid value of the B chain is 50 to 250 mgKOH / g and the number average molecular weight is 1,000 to 11,000; At least a portion of the carboxy groups in the B chain is neutralized with an alkali.

[0039] The number average molecular weight (Mn) of the AB block copolymer is preferably 10,000 to 60,000, more preferably 10,000 to 30,000. By setting the number average molecular weight within the above range, it is possible to form an image that has better adhesion to polyolefin-based plastic films and the like and is a printed film with better abrasion resistance. If the number average molecular weight of the AB block copolymer is less than 10,000, the effect of improving the physical properties of the film formed may be somewhat insufficient. On the other hand, if the number average molecular weight of the AB block copolymer is more than 60,000, the polymerization of the AB block copolymer may take a long time, and problems such as the particle size of the resin particles formed by the AB block copolymer becoming excessively large may occur.

[0040] The molecular weight distribution (weight average molecular weight (Mw) / number average molecular weight (Mn) (hereinafter also referred to as "PDI") of the AB block copolymer is preferably 1.8 or less, and more preferably 1.6 or less. If the molecular weight distribution (PDI) of the AB block copolymer exceeds 1.8, the copolymer will contain a wide range of molecular weights, from small to large, making it somewhat difficult to form a coating with excellent adhesion to plastic films.

[0041] The acid value of the AB block copolymer is preferably 20 to 100 mgKOH / g. If the acid value of the AB block copolymer is less than 20 mgKOH / g, the B chain is less soluble in water, and it may be difficult to disperse and emulsify the AB block copolymer in an aqueous medium. On the other hand, if the acid value of the AB block copolymer is more than 100 mgKOH / g, the water resistance and chemical resistance of the film may be slightly reduced.

[0042] The A chain constituting the AB block copolymer is a polymer chain (polymer block) that becomes a durable water-insoluble coating. The structural unit (A) in the A chain is a structural unit that exhibits adhesion and affinity with plastic films and improves the strength of the coating. Furthermore, the structural unit (A) is a structural unit that contributes to the softness and plasticity of the coating, the affinity and adhesion with the substrate, and the affinity with the binder component.

[0043] The content of the structural unit (A) in the A chain is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass. That is, it is particularly preferable that the A chain is substantially composed of only the structural unit (A). However, the A chain may further have other structural units other than the structural unit (A) so long as the content is less than 20% by mass. As the monomer constituting the other structural units, a methacrylate-based monomer (other methacrylate-based monomer) other than the methacrylate-based monomer constituting the structural unit (A) can be used. Other methacrylate monomers include methacrylic acid alkyl esters such as butyl methacrylate, t-butyl methacrylate, and hexyl methacrylate; alicyclic methacrylic acid alkyl esters such as dicyclopentanyl methacrylate; glycol methacrylic acid esters such as 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, butoxyethyl methacrylate, dicyclopentenyloxyethyl methacrylate, polyethylene glycol monomethacrylate, and polyethylene glycol monomethyl ether methacrylate; and amino group-containing methacrylates such as dimethylaminoethyl methacrylate and diethylaminoethyl methacrylate.

[0044] The A chain may further have a structural unit derived from methacrylic acid. However, the content of the structural unit derived from methacrylic acid in the A chain is preferably within a range in which the A chain does not dissolve in water even after neutralization. That is, the acid value of the A chain is preferably 50 mg KOH / g or less, more preferably 30 mg KOH / g or less. The A chain may further have a structural unit derived from a methacrylate having a polyethylene glycol chain. However, the content of the structural unit derived from a methacrylate having a polyethylene glycol chain in the A chain is preferably within a range in which the A chain does not dissolve in water.

[0045] The glass transition temperature (Tg) of the A chain is preferably 150° C. or lower, and more preferably 110° C. or lower. By setting the glass transition temperature of the A chain to 150° C. or lower, it is possible to obtain an AB block copolymer capable of forming a film having further improved properties such as softness, flexibility, film conformability, abrasion resistance, and film-forming property.

[0046] In this specification, the term "glass transition temperature (Tg)" refers to a value (theoretical value) calculated from the glass transition temperature (Tg) of a homopolymer. For example, for a polymer (copolymer) in which x types of monomers are copolymerized, the mass (g) of each monomer is expressed as "W 1 , W 2 , W x " The glass transition temperature (Tg (℃)) of the homopolymer of each monomer is defined as "T 1 , T 2 , T x " If this assumption is made, the glass transition temperature (T (°C)) of this copolymer can be calculated from the following formula (X). 1 / T =W 1 / (T 1 +273)+W 2 / (T 2 +273)+···W x / (T x +273) (X)

[0047] For the glass transition temperature (Tg (°C)) of the homopolymer, the value described in "Polymer Handbook, 4th Edition" or values ​​from various other documents may be used. In this specification, the value described in "Polymer Handbook, 4th Edition" is used.

[0048] The A chain is a water-insoluble polymer chain that forms particles in an aqueous medium. Even if a polymer emulsion obtained by using an AB block copolymer having such an A chain is added to an ink as a binder component, the viscosity of the ink is not excessively increased, and the ejection stability of the ink can be maintained in a good state. In addition, since the AB block copolymer is substantially insoluble in water, a printing film that exhibits higher adhesion to a substrate such as a plastic film can be formed by using an ink containing a polymer emulsion obtained by using this AB block copolymer as a binder component.

[0049] The number average molecular weight (Mn) of the A chain is preferably 3,000 to 50,000, and more preferably 4,000 to 40,000. By setting the number average molecular weight of the A chain within the above range, a coating film with better performance such as adhesion and abrasion resistance can be formed. If the number average molecular weight of the A chain is less than 3,000, the adhesion of the formed coating film to plastic films and the like may be slightly reduced. On the other hand, if the number average molecular weight of the A chain exceeds 50,000, the particle size may become too large, and the polymerization time may become long due to the high molecular weight.

[0050] The molecular weight distribution (PDI) of the A chain is preferably 1.8 or less, more preferably 1.5 or less. If the molecular weight distribution (PDI) of the A chain exceeds 1.8, the A chain will contain a wide range of molecular weights from small to large, making it somewhat difficult to form a coating with excellent adhesion to plastic films.

[0051] The B chain constituting the AB block copolymer is a polymer chain (polymer block) having a structural unit (B-1) derived from methacrylic acid. That is, since the B chain has a carboxy group, it is a polymer chain that has an affinity for water and dissolves. In an aqueous medium, the water-insoluble A chain becomes particles, and the B chain dissolved in water stabilizes the particles of the A chain. This allows the AB block copolymer to be emulsified and dispersed in an aqueous medium. In addition, since the B chain dissolves in water, even if it is dried, it has the property of dissolving the AB block copolymer in water again (re-solubility). Furthermore, since the carboxy group forms hydrogen bonds with a substrate such as a plastic film, a coating with excellent adhesion can be formed.

[0052] The acid value of the B chain is preferably 50 to 250 mgKOH / g, more preferably 55 to 200 mgKOH / g, and particularly preferably 60 to 150 mgKOH / g. If the acid value of the B chain is less than 50 mgKOH / g, the B chain is less soluble in water, and it may be difficult to disperse and emulsify the AB block copolymer in an aqueous medium. On the other hand, if the acid value of the B chain is more than 250 mgKOH / g, the B chain is too hydrophilic, and the water resistance and chemical resistance of the coating may be easily reduced.

[0053] In the B chain, the content of the structural unit (B-2) is preferably 80% by mass or more, more preferably 90% by mass or more, and particularly preferably 100% by mass, based on the total content of structural units other than the structural unit (B-1). That is, it is preferable that the portion of the B chain other than the structural unit (B-1) is substantially composed only of the structural unit (B-2). The B chain having the structural unit (B-2) has good compatibility with the A chain.

[0054] The B chain may further have other structural units other than the structural units (B-1) and (B-2). As the monomer constituting the other structural units, a methacrylate monomer (other methacrylate monomer) other than the methacrylate monomer constituting the structural unit (B-2) can be used. As the other methacrylate monomer, the same as the above-mentioned "other methacrylate monomer" can be mentioned.

[0055] The number average molecular weight (Mn) of the B chain is preferably 1,000 to 11,000, and more preferably 2,000 to 10,000. If the number average molecular weight of the B chain is less than 1,000, the water-soluble B chain is too short, which may reduce the dispersibility and emulsifiability of the particulated A chain and increase the overall particle size. On the other hand, if the number average molecular weight of the B chain exceeds 11,000, the hydrophilicity becomes too high, which may reduce the water resistance of the formed film and may cause the viscosity of the ink to become excessively high when the B chain is blended with ink or the like.

[0056] The AB block copolymer can be synthesized according to a conventional method. Among them, it is preferable to synthesize it by a polymerization method having living properties such as a living anionic polymerization method, a living cationic polymerization method, and a living radical polymerization method, and it is particularly preferable to synthesize it by a living radical polymerization method from the viewpoints of conditions, materials, and equipment. Examples of living radical polymerization methods include atom transfer radical polymerization method (ATRP method), reversible addition-fragmentation chain transfer polymerization method (RAFT method), nitroxide method (NMP method), organotellurium method (TERP method), reversible transfer catalysis polymerization method (RTCP method), and reversible catalyst-mediated polymerization method (RCMP method). Among them, the RTCP method and the RCMP method, which use an organic compound as a catalyst and an organic iodide as a polymerization initiator compound, are preferable. These methods use relatively safe commercially available compounds, do not use heavy metals or special compounds, and are advantageous in terms of cost and purification. Furthermore, by making the growth terminal a tertiary iodine, a block structure with good accuracy can be easily formed with general equipment.

[0057] The polymerization may be either thermal polymerization or photopolymerization, and an azo-based radical generator, a peroxide-based radical generator, a photosensitizer, etc. may be added to the polymerization reaction system. The polymerization method may be any of solventless polymerization, solution polymerization, and emulsion polymerization, among which solution polymerization is preferred. When the obtained AB block copolymer is dispersed in an aqueous medium to produce a polymer emulsion, it is preferable to use the same organic solvent as the water-soluble organic solvent used in the aqueous medium during solution polymerization, since the reaction liquid after the polymerization reaction can be used as it is.

[0058] Either the A chain or the B chain may be polymerized first. However, if the B chain is polymerized first, methacrylic acid may remain in the polymerization system. In this case, a structural unit derived from methacrylic acid may be introduced into the A chain that is polymerized thereafter, so it is preferable to polymerize the A chain first and then the B chain.

[0059] Methods for neutralizing, emulsifying, and dispersing an AB block copolymer are well known. For example, after synthesizing an AB block copolymer by solution polymerization, alkaline water can be added to the polymerization solution while stirring it to disperse and emulsify it. In addition, the AB block copolymer extracted after polymerization by a method such as (i) drying, (ii) precipitating in a poor solvent, or (iii) neutralizing and dissolving in water, followed by precipitating by adding an acid, may be neutralized and emulsified and dispersed in water, and may be heated as necessary.

[0060] At least a part of the carboxyl groups in the B chain is neutralized with an alkali. Examples of the alkali include ammonia; aliphatic primary to tertiary amines such as monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, and triethylamine; alcohol amines such as monoethanolamine, diethanolamine, triethanolamine, monopropanolamine, dipropanolamine, tripropanolamine, methylethanolamine, dimethylethanolamine, and methylisopropylamine; heterocyclic amines such as piperidine, morpholine, and N-methylmorpholine; and alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide. Among these, at least one selected from the group consisting of ammonia, dimethylaminoethanol, 2-amino-1-propanol, sodium hydroxide, potassium hydroxide, lithium hydroxide, linear aliphatic amines having 6 to 22 carbon atoms, branched aliphatic amines having 6 to 22 carbon atoms, and unsaturated aliphatic amines having 6 to 22 carbon atoms is preferable. The amount of alkali is preferably an amount that neutralizes a part or all of the acidic groups, such as the carboxyl groups, in the AB block copolymer.

[0061] (Pigments) As the pigment, conventionally known organic pigments and inorganic pigments that are blended in aqueous inks for inkjet recording can be used. As the organic pigment, chromatic pigments such as phthalocyanine, azo, azomethine azo, azomethine, anthraquinone, perinone-perylene, indigo-thioindigo, dioxazine, quinacridone, isoindoline, isoindolinone, diketopyrrolopyrrole, quinophthalone, and indanthrene pigments; carbon black pigments such as furnace black, lamp black, acetylene black, and channel black; and the like can be mentioned. As the inorganic pigment, extender pigments, titanium oxide pigments, iron oxide pigments, and spinel pigments can be mentioned.

[0062] Unless the printed matter (image) requires hiding power, it is preferable to use organic fine particle pigments. When a printed matter showing high definition and transparency is required, it is preferable to use pigments that have been finely milled by wet grinding such as salt milling or dry grinding. Considering the avoidance of nozzle clogging, it is preferable to use organic pigments with a number average particle size of 0.2 μm or less, or inorganic pigments with a number average particle size of 0.4 μm or less, from which pigments with particle sizes exceeding 1.0 μm have been removed.

[0063] Examples of pigments, listed by Color Index (CI) number, are: CI Pigment Yellow 12, 13, 14, 17, 20, 24, 74, 83, 86, 93, 94, 95, 97, 109, 110, 117, 120, 125, 128, 129, 137, 138, 139, 147, 148, 150, 151, 153, 154, 155, 166, 168, 175, 180, 181, 185, 191; CI Pigment Orange 16, 36, 43, 51, 55, 59, 61, 64, 71, 73; CI Pigment Red 4, 5, 9, 23, 48, 49, 52, 53, 57, 97, 112, 122, 123, 14 4, 146, 147, 149, 150, 166, 168, 170, 176, 177, 180, 184, 185, 192, 202, 207, 214, 215, 216, 217, 220, 221, 223, 224, 226, 227, 228, 238, 240, 242, 254, 255, 264, 269, 272; CI Pigment Violet 19, 23, 29, 30, 37, 40, 50; CI Pigment Blue 15, 15:1, 15:3, 15:4, 15:6, 22, 60, 64; CI Pigment Green 7, 36; CI Pigment Black 7; CI Pigment White 6; and the like.

[0064] From the viewpoints of color development, dispersibility, weather resistance, and the like, preferred are yellow pigments such as CI Pigment Yellow 74, 83, 109, 128, 139, 150, 151, 154, 155, 180, 181, and 185; red pigments such as CI Pigment Red 122, 170, 176, 177, 185, and 269, and CI Pigment Violet 19 and 23; blue pigments such as CI Pigment Blue 15:3, 15:4, and 15:6; black pigments such as CI Pigment Black 7; and white pigments such as CI Pigment White 6.

[0065] The pigment may be any of the following: an untreated pigment; a self-dispersing pigment having a functional group introduced on its surface; a treated pigment having been surface-treated with a surface treatment agent such as a coupling agent or an activator, or a polymer, or encapsulated. A self-dispersing pigment is an easily dispersible pigment having acidic groups such as a carboxy group, a sulfonic acid group, and a phosphoric acid group introduced on the surface of the pigment particle, and these acidic groups are neutralized to make the pigment more compatible with water, thereby making the pigment easily dispersible in ink without using a pigment dispersant. In contrast, it is preferable to use a pigment dispersant in combination with untreated pigments, surface-treated pigments, and encapsulated pigments.

[0066] The content of the pigment in the aqueous ink is preferably from 0.1 to 25% by mass, and more preferably from 0.2 to 20% by mass, based on the total amount of the ink.

[0067] (Pigment dispersant) When a pigment other than a self-dispersing pigment is used, the aqueous ink preferably further contains a pigment dispersant for dispersing the pigment in the ink. For example, the aqueous ink preferably further contains a pigment dispersant in a finely dispersed or dissolved state, the pigment dispersant being a vinyl polymer having a number average molecular weight of 1,000 to 20,000 and an acid value of 50 to 250 mg neutralized with an alkaline substance.

[0068] The vinyl polymer preferably has an acidic group such as a carboxy group, a sulfonic acid group, or a phosphoric acid group. The acidic group such as a carboxy group can be neutralized with an alkaline substance to make it compatible with water and finely dispersed or dissolved in the ink. The vinyl polymer having an acidic group has a structural unit derived from a monomer having an acidic group. Examples of the monomer having an acidic group include (meth)acrylic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, styrene carboxylic acid, a monomer obtained by reacting a (meth)acrylate monomer having a hydroxyl group with an anhydrous carboxylic acid, a dibasic acid, or a polycarboxylic acid to form a monoester, vinyl sulfonic acid, acrylamidomethylpropyne sulfonic acid, vinyl phosphoric acid, and methacryloyloxyethyl phosphoric acid.

[0069] The vinyl polymer has a constituent unit derived from a vinyl monomer. Examples of the vinyl monomer include aromatic vinyl monomers such as styrene, vinyl toluene, and vinyl naphthalene; acrylate monomers such as butyl acrylate and 2-ethylhexyl acrylate; the above-mentioned "other methacrylate monomers;" vinyl ester monomers such as vinyl acetate; and heterocyclic vinyl monomers such as vinyl pyridine and vinyl imidazole.

[0070] Specific examples of vinyl polymers include styrene-acrylic acid copolymer, styrene-maleic acid copolymer, styrene-ethyl acrylate-acrylic acid copolymer, styrene-acrylic acid-ethoxyethyl acrylate copolymer, styrene-methacrylic acid copolymer, styrene-methacrylic acid-2-hydroxyethyl methacrylate copolymer, methacrylic acid-benzyl methacrylic acid copolymer, styrene-methacrylic acid-dimethylaminoethyl methacrylate-butyl acrylate copolymer, styrene-maleic acid-polyethylene glycol propylene glycol monobutyl ether monoamine amidation copolymer of maleic acid, and styrene-methyl methacrylate-2-ethylhexyl methacrylate-methacrylic acid copolymer.

[0071] The number average molecular weight (Mn) of the vinyl polymer used as the pigment dispersant is preferably 1,000 to 20,000, more preferably 3,000 to 15,000, and particularly preferably 5,000 to 13,000. If the number average molecular weight of the vinyl polymer is less than 1,000, the adsorption to the pigment may be insufficient and the strength of the printed film formed may be reduced. On the other hand, if the number average molecular weight of the vinyl polymer is more than 20,000, the viscosity of the ink may increase excessively and the ink may easily exhibit a non-Newtonian viscosity, resulting in a decrease in the ejection stability of the ink.

[0072] The acid value of the vinyl polymer used as the pigment dispersant is preferably 50 to 250 mgKOH / g, more preferably 75 to 150 mgKOH / g, and particularly preferably 85 to 130 mgKOH / g. If the acid value of the vinyl polymer is less than 50 mgKOH / g, it may be difficult to dissolve in water even when neutralized with an alkaline substance, and the function as a pigment dispersant may be insufficient. On the other hand, if the acid value of the vinyl polymer is more than 250 mgKOH / g, the water solubility may be too high. As a result, the viscosity of the ink increases excessively, and the amount of hydrophilic acidic groups such as carboxyl groups increases, so that the water resistance of the formed printing film may decrease.

[0073] The vinyl polymer can be synthesized according to a conventional method. For example, in the presence of an azo initiator such as azobisisobutyronitrile or a peroxide initiator such as benzoyl peroxide, a vinyl polymer can be obtained by bulk polymerization of a monomer alone, emulsion polymerization, or solution polymerization using a water-soluble organic solvent for inkjet ink. The obtained vinyl polymer can be neutralized with an alkaline substance to form a pigment dispersant. In addition, a solution of the pigment dispersant may be mixed with a pigment, and then added to a poor solvent or treated with an acid to precipitate the pigment dispersant, and the pigment may be treated or encapsulated to prepare a polymer-treated pigment. A living radical polymerization method is preferred as a polymerization method for producing a vinyl polymer. The vinyl polymer may be any of polymers having a higher structure such as a random copolymer, a block copolymer, a graft copolymer, a gradient copolymer, a star polymer, and a dendrimer.

[0074] (aqueous medium) The aqueous ink of the present embodiment is an aqueous ink containing an aqueous medium that is a mixed solvent of water and a water-soluble organic solvent. As the water, ion-exchanged water, distilled water, purified water, etc. are preferably used. The content of water in the aqueous ink is preferably 30 to 90% by mass based on the total amount of the ink.

[0075] Considering printing on plastic films with low ink permeability, it is preferable to use a water-soluble organic solvent that not only functions as a humectant but also has good wettability to the plastic film. It is also preferable to use a water-soluble organic solvent that can function as a leveling agent for the surface of the printing substrate and also as a film-forming assistant that improves the film-forming properties of the binder in the ink.

[0076] Examples of the water-soluble organic solvent include alcohol-based solvents such as methanol, ethanol, and isopropanol; ketone-based solvents such as acetone; alkylene glycol-based solvents such as ethylene glycol, diethylene glycol, propylene glycol, and dipropylene glycol; alkylene glycol monoalkyl ether-based solvents such as ethylene glycol methyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, and tripropylene glycol monomethyl ether; glycerin-based solvents such as glycerin, diglycerin, and ethylene oxide adducts of glycerin; amide-based solvents such as 2-pyrrolidone, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropionamide, and 3-butoxy-N,N-dimethylpropionamide; urea-based solvents such as tetramethylurea and dimethylimidazolidinone; carbonate-based solvents such as ethylene carbonate and dimethyl carbonate; and the like.

[0077] If a large amount of water-soluble organic solvent remains in the printing film formed by the binder in the ink applied to the printing substrate, the water resistance, adhesion to the printing substrate, and abrasion resistance of the printing film may decrease. In addition, the organic solvent used in synthesizing the binder by a method such as solution polymerization may be directly blended into the ink. For this reason, it is preferable to use a water-soluble organic solvent with a certain degree of volatility. Specifically, the water-soluble organic solvent preferably contains propylene glycol (boiling point 188°C) and at least one selected from the group consisting of diethylene glycol monobutyl ether (boiling point 230°C), propylene glycol monomethyl ether (boiling point 121°C), propylene glycol monoethyl ether (boiling point 132.8°C), propylene glycol monopropyl ether (boiling point 150°C), and dipropylene glycol monomethyl ether (boiling point 189.6°C).

[0078] The content of the water-soluble organic solvent in the aqueous ink is preferably 3 to 30% by mass, more preferably 5 to 25% by mass, based on the total amount of the ink. If the content of the water-soluble organic solvent is less than 3% by mass, the ink may be easily dried and may not function as a leveling agent on the surface of the plastic film. On the other hand, if the content of the water-soluble organic solvent is more than 30% by mass, the viscosity of the ink may increase, the ejection property of the ink may decrease, and the stability of the ink may easily decrease. In addition, the binder may precipitate or the pigment may aggregate. Furthermore, if the content of the water-soluble organic solvent is too high, the water-soluble organic solvent may easily remain in the printing film, so blocking may easily occur and the physical properties such as water resistance and abrasion resistance of the image may slightly decrease.

[0079] (wax) The water-based ink of the present embodiment contains a wax. By including a wax, an image can be formed that is a printed film having excellent durability and adhesion to a plastic film. The wax is preferably included in the water-based ink in the form of particles. In other words, the wax is preferably blended in the water-based ink in the form of a wax emulsion.

[0080] As the wax, it is preferable to use polyethylene wax. Since polyethylene wax has a high affinity for plastic films such as polyolefin-based films, it is possible to form a printed film with improved adhesion to the plastic film. Furthermore, since polyethylene wax has a high hydrophobicity, it is possible to form a printed film with superior durability. The content of the wax in the aqueous ink is preferably 0.1 to 2.5% by mass, more preferably 0.3 to 1.5% by mass, based on the total mass of the ink.

[0081] (Surfactant) The aqueous ink of this embodiment contains a surfactant. By using the surfactant, the surface tension of the aqueous ink can be maintained within an appropriate range. The surface tension of the ink is preferably 15 to 45 mN / m, and more preferably 20 to 40 mN / m.

[0082] Examples of the surfactant include silicone surfactants, acetylene glycol surfactants, fluorine surfactants, alkylene oxide surfactants, and hydrocarbon surfactants, etc. Among them, it is preferable to use at least one selected from the group consisting of silicone surfactants, acetylene glycol surfactants, and fluorine surfactants.

[0083] Generally, surfactants can cause the ink to foam or be repelled by the film surface. Furthermore, the use of surfactants can also cause the pigment to easily aggregate. For this reason, it is preferable to appropriately adjust the content of the surfactant. Specifically, the content of the surfactant in the aqueous ink is preferably 3.5% by mass or less, more preferably 0.01 to 2.0% by mass, based on the total mass of the ink.

[0084] (Other Ingredients) The water-based ink may further contain components other than the above-mentioned components (other components) as necessary. Examples of the other components include organic solvents other than the above-mentioned water-soluble organic solvents, preservatives, leveling agents, surface tension adjusters, pH adjusters, UV absorbers, light stabilizers, antioxidants, dyes, fillers, thickeners, defoamers, antifungal agents, antistatic agents, metal particles, magnetic powders, and other various additives.

[0085] (Water-based ink manufacturing) The ink of this embodiment can be manufactured according to a conventional method. The following is an example of a series of steps for manufacturing the aqueous ink of this embodiment. First, a pigment dispersion (pigment dispersion) containing a pigment and a pigment dispersant is prepared. Specifically, a mixture containing water, a pigment, and a pigment dispersant, and further containing a water-soluble organic solvent as necessary, is obtained. The mixture obtained is treated using a paint shaker, a ball mill, an attritor, a sand mill, a horizontal media mill, a colloid mill, a roll mill, or the like, and the pigment is finely dispersed to prepare a pigment dispersion. Next, water, a polyhydroxy polyurethane resin, an acrylic polymer, a water-soluble organic solvent, a surfactant, a wax, and other additives used as necessary are added to the obtained pigment dispersion, and an alkali or the like is further added to adjust the pH. Furthermore, various additives such as a surfactant and a preservative are added as necessary to obtain the desired aqueous ink. It is preferable to remove coarse particles and aggregates from the pigment dispersion or the aqueous ink by centrifugal separation or filtration with a filter.

[0086] The viscosity of the aqueous ink is adjusted according to the type of pigment, etc., so that the ink can be ejected from the nozzles of the recording head by the inkjet method. For example, when an organic pigment is used, the viscosity of the aqueous ink is preferably 2 to 10 mPa·s. When an inorganic pigment is used, the viscosity of the aqueous ink is preferably 5 to 30 mPa·s.

[0087] The pH of the ink is preferably 7.0 to 10.0, and more preferably 7.5 to 9.5. If the pH of the ink is less than 7.0, the binder may be more likely to precipitate and the pigment may be more likely to aggregate. On the other hand, if the pH of the ink is more than 10.0, the ink may be difficult to handle because of its strong alkalinity.

[0088] (Printing base material) By using the aqueous ink of this embodiment, images can be recorded (printed) on various printing substrates by the inkjet recording method. In particular, by using the aqueous ink of this embodiment, a printing film excellent in adhesion and durability such as abrasion resistance can be formed even on polyolefin-based plastic films such as polyethylene and polypropylene. For this reason, the aqueous ink of this embodiment is suitable as an ink for printing images on plastic films by the inkjet recording method.

[0089] As the film to be used as the printing substrate, a plastic film formed from various resins such as polyolefin-based, polyester-based, polyamide-based, polyvinyl halide-based, cellulose-based, polystyrene-based, polymethacrylate-based, polyacrylonitrile-based, polycarbonate-based, polyimide-based, polyvinyl acetal-based, and polyvinyl alcohol-based resins can be used.

[0090] Examples of polyolefin resins include low-density polyethylene, medium-density polyethylene, high-density polyethylene, polypropylene, polyα-olefin, polyethylene vinyl acetate, polyethylene vinyl alcohol, and polycycloolefin. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, and polylactic acid. Examples of polyamide resins include nylon 6, nylon 66, and nylon 610. Examples of polyvinyl halide resins include polyvinyl chloride, polyvinylidene chloride, and polyfluoroethylene. Among them, it is preferable to print on a polyolefin resin film, which is inexpensive and easily available, and on which a printing film having excellent adhesion and abrasion resistance is generally not easily formed, and it is more preferable to print on a polyethylene resin film or a polypropylene resin film.

[0091] The plastic film may be unstretched or may be stretched by uniaxial stretching, biaxial stretching, or the like. The surface (printed surface) of the plastic film may be untreated or may be surface-treated by plasma treatment, corona treatment, radiation treatment, silane coupling treatment, or the like. The plastic film may have a single-layer structure or a multi-layer structure, and may be aluminum-vapor-deposited or transparently vapor-deposited. The thickness of the plastic film is preferably 1 to 500 μm, and more preferably 5 to 200 μm. The plastic film may be colored with a pigment or dye, or may contain a reinforcing filler such as carbon black, silica, calcium carbonate, glass fiber, or cellulose nanofiber. EXAMPLES

[0092] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0093] <Production of Cyclic Carbonate Compound> (Production Example 1) 100 parts of bisphenol A diglycidyl ether (trade name "jER828", manufactured by Japan Epoxy Resins Co., Ltd., epoxy equivalent: 192 g / eq) (jER828), 20 parts of sodium iodide (manufactured by Wako Pure Chemical Industries, Ltd.), and 100 parts of N-methyl-2-pyrrolidone (NMP) were placed in a reaction vessel. Carbon dioxide was continuously blown into the contents while stirring, and the contents were heated to 100°C and reacted for 10 hours. 1,400 parts of isopropanol was added, and the precipitate that separated out was collected by filtration. The precipitate obtained was recrystallized using toluene to obtain 52 parts of a white powder (yield 42%).

[0094] The powder obtained was analyzed using a Fourier transform infrared spectrophotometer (FT-IR) (trade name "FT-720", manufactured by Horiba, Ltd.). As a result, the 910 cm -1 The absorption around 1,800 cm due to the carbonyl group of the cyclic carbonate disappears, and -1It was confirmed that absorption occurred around the polarity of the powder. The powder was analyzed using high performance liquid chromatography (HPLC) (product name "LC-2000", manufactured by JASCO Corporation, column: product name "FinepakSIL C18-T5", mobile phase: acetonitrile + water). As a result, it was confirmed that the peak of the raw material disappeared and a new peak appeared on the high polarity side. The purity of the powder was 98%. Furthermore, the melting point was 178°C and the melting point range was ±5°C as a result of DSC measurement.

[0095] From the above, it was confirmed that the obtained powder was compound IA having a structure represented by the following formula (IA). In the chemical structure of compound IA, the proportion (calculated value) of components derived from carbon dioxide was 20.5%.

[0096] TIFF2025047711000006.tif46170

[0097] <Synthesis of polyhydroxy polyurethane resin> (Synthesis Example 1) 10 parts of bisphenol A diglycidyl ether (jER828), 30.1 parts of hexamethylenediamine (HMD), and 99 parts of tetrahydrofuran (THF) were placed in a reaction vessel. The contents were heated to 60°C with stirring and reacted for 12 hours. 100 parts of compound I-A obtained in Production Example 1 was added, and the reaction was carried out at 60°C for 24 hours with stirring. The liquid after the reaction (intermediate solution) was analyzed using FT-IR. As a result, a peak at 1,800 cm originating from the carbonyl group of the cyclic carbonate was observed. -1 The absorption around 1,760 cm originating from the carbonyl group of the urethane bond disappears, and -1 It was confirmed that absorption occurred around this point. In addition, the amine value of the intermediate in the intermediate solution (converted value for 100% resin content) measured in accordance with JIS K 1557 was 20.1 mgKOH / g.

[0098] The intermediate solution was diluted with 121 parts of THF, and then 5.1 parts of maleic anhydride was added and reacted at room temperature (25°C). Analysis was performed using FT-IR, and the 1,800 cm -1 The reaction was terminated after confirming that the absorption around the area had disappeared. The acid value measured according to JIS K 2501 was 20.1 mgKOH / g. After adding 3.5 parts of 28% ammonia water to neutralize the carboxyl group, 392 parts of ion-exchanged water was gradually added while stirring at room temperature to perform phase inversion emulsification. The reaction vessel was heated to 50°C and reduced pressure, and the THF was distilled off, and the solid content was adjusted to 25%, to obtain a water dispersion of polyhydroxy polyurethane resin PU-1 that was uniform in appearance. The number average particle size of the resin particles in the water dispersion measured using a dynamic light scattering particle size distribution measuring device (particle size measuring device, product name "nanoSAQRA", manufactured by Otsuka Electronics Co., Ltd.) was 53 nm. The hydroxyl value of polyhydroxy polyurethane resin PU-1 measured according to JIS K 1557-1 was 200.7 mgKOH / g in terms of solid content. The polyhydroxy polyurethane resin PU-1 had a weight average molecular weight (Mw) of 78,000 in terms of polystyrene, as measured by gel permeation chromatography (GPC) using THF as a developing solvent.

[0099] (Synthesis Examples 2 to 4) Except for using the formulations shown in Table 1, the same procedures as in Synthesis Example 1 described above were carried out to obtain water dispersions of polyhydroxy polyurethane resins PU-2 to PU-4.

[0100] TIFF2025047711000007.tif118170

[0101] <Synthesis of acrylic polymer> (Synthesis Example 5) Into a reaction vessel, 172.4 parts of diethylene glycol monobutyl ether (BDG), 1.0 part of iodine, 3.7 parts of 2,2-azobis(4-methoxy-2,4-dimethylvaleronitrile) (trade name "V-70", Fujifilm Wako Pure Chemical Industries, Ltd.) (V-70), 0.2 parts of N-iodosuccinimide (NIS), 50 parts of tetrahydrofurfuryl methacrylate (THFMA), and 50 parts of isobornyl methacrylate (IBXMA) were placed. THFMA is a methacrylate synthesized using tetrahydrofurfuryl alcohol obtained by hydrogenating furfural obtained from corn cobs, etc., and is a methacrylate synthesized using alcohol derived from plant raw materials. IBXMA is a methacrylate synthesized using borneol obtained from pine resin or pine essential oil, and is a methacrylate synthesized using alcohol derived from plant raw materials. The mixture was stirred while bubbling nitrogen, and polymerized at 45°C for 4 hours to form a polymer (A chain). The solid content measured by sampling a portion of the reaction solution was 37.4%, and the polymerization conversion calculated based on the solid content was about 100%. The number average molecular weight (Mn) of the A chain measured in terms of polystyrene by GPC using THF as the developing solvent was 8,500, and the dispersity (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) was 1.33. The glass transition temperature (Tg) of the A chain calculated from the above formula (X) was 102 ° C. The Tg of the THFMA homopolymer was set to 60 ° C., and the Tg of the IBXMA homopolymer was set to 155 ° C.

[0102] After cooling the obtained solution of A chain to 40 ° C, 2.0 parts of V-70, 17 parts of THFMA, 52 parts of IBXMA, and 17 parts of methacrylic acid (MAA) were added. Polymerization was performed at 40 ° C for 4 hours to form B chain, and an AB block copolymer was obtained. The amount of residual monomer was measured by gas chromatography, and it was confirmed that the polymerization reaction was almost complete. A part of the reaction solution was sampled and measured for solid content to be about 50%, and the polymerization conversion rate was about 100%. The Mn of the obtained AB block copolymer was 15,000 and the PDI was 1.42. The GPC peak of A chain shifted to the high molecular weight side, and it was confirmed that an AB block copolymer was obtained. The Mn of B chain was 6,500. The acid value of B chain calculated from the amount of MAA used was 112 mg KOH / g. A part of the reaction solution was added to methanol, and the precipitate formed was filtered and washed with methanol, and then dried to obtain a sample. The acid value of the obtained sample was measured by titration with an ethanolic 0.1N potassium hydroxide solution and was found to be 52 mgKOH / g.

[0103] At room temperature, a mixture of 10.2 parts of 28% ammonia water and 334.7 parts of ion-exchanged water was added to neutralize and emulsify the mixture. Water was added to adjust the solid content to 25%, to obtain an emulsion of acrylic polymer A-1.

[0104] (Synthesis Examples 6 to 8) Emulsions of acrylic polymers A-2 to A-4 were obtained in the same manner as in Synthesis Example 5 above, except that the formulations were as shown in Table 2. The meanings of the abbreviations in Table 2 are as follows. EMA: Ethyl methacrylate BzMA: Benzyl methacrylate HEMA: 2-hydroxyethyl methacrylate

[0105] TIFF2025047711000008.tif224170

[0106] <Production of pigment dispersants> (Production Example 2) 100 parts of BDG was placed in a reaction vessel, and heated to 80°C by bubbling nitrogen. 20 parts of styrene (St), 15 parts of methyl methacrylate (MMA), 15 parts of EMA, 20 parts of EHMA, 15 parts of HEMA, 15 parts of MAA, and 1.5 parts of 2,2-azobisisobutyronitrile (AIBN) were placed in a separate vessel and stirred to prepare a homogeneous monomer solution. The prepared monomer solution was dropped into the reaction vessel over 2 hours. One hour after the dropwise addition, 1.5 parts of AIBN were added, and the reaction was continued for another 5 hours at 80°C. After cooling, a mixture of 11.6 parts of 28% ammonia water and 62.7 parts of ion-exchanged water was added to obtain an aqueous solution of pigment dispersant G-1, which is a light brown transparent polymer solution. The obtained pigment dispersant G-1 (polymer) had an Mn of 13,200, a PDI of 2.15, and an acid value of 65.2 mgKOH / g. The aqueous solution of pigment dispersant G-1 had a pH of 8.7 and a solid content of 36.5%.

[0107] <Production of Water-Based Pigment Dispersion> (Production Example 3) 864 parts of ion-exchanged water, 411 parts of an aqueous solution of pigment dispersant G-1 (150 parts of polymer), and 600 parts of CI Pigment Blue 15:3 (trade name "PB15:3", manufactured by Dainichiseika Chemicals Co., Ltd.) were mixed and thoroughly stirred using a dissolver to obtain a mixture. The obtained mixture was placed in a horizontal media disperser (trade name "Dyno Mill 0.6 liter multi-lab", manufactured by Shinmaru Enterprises, zirconia bead diameter: 0.5 mm), and the pigment was thoroughly dispersed in the mill base by dispersion treatment at a peripheral speed of 7 m / s. After centrifugal separation (7,500 rpm, 20 minutes), coarse particles were removed by filtration through a 10 μm membrane filter. The concentration was adjusted by adding ion-exchanged water to obtain a blue aqueous pigment dispersion B-1 with a pigment concentration of 14%.

[0108] <Production of Water-Based Ink for Inkjet Recording> (Examples 1 to 10, Comparative Examples 1 to 4) The components were mixed according to the formulations shown in Tables 3 and 4. The mixture was filtered through a 5 μm membrane filter to remove coarse particles, to obtain a water-based ink for ink-jet recording.

[0109] TIFF2025047711000009.tif127170

[0110] TIFF2025047711000010.tif148170

[0111] <Evaluation> (Ink properties) The number average particle size of the pigment in the aqueous ink and the viscosity of the aqueous ink were measured initially (immediately after preparation) and after storage at 70°C for one week. The results are shown in Table 5. The number average particle size of the pigment was measured using a dynamic light scattering particle size distribution measuring device (particle size measuring device, product name "nanoSAQRA", manufactured by Otsuka Electronics Co., Ltd.). The viscosity of the aqueous ink was measured using a B-type viscometer.

[0112] In addition, the particle size change rate (%) and viscosity change rate (%) were calculated from the measured number average particle size of the pigment and the viscosity of the water-based ink. The results are shown in Table 5. Furthermore, the physical properties of the ink were evaluated according to the following evaluation criteria. The results are shown in Table 5. ◯: Even after storage at 70° C. for one week, the absolute value of the rate of change in particle size and the absolute value of the rate of change in viscosity were both less than 15%. Δ: After storage at 70° C. for one week, the absolute value of the rate of change in particle size or the absolute value of the rate of change in viscosity was 15% or more and less than 30%. ×: The pigment was finely dispersed immediately after preparation, but after storage at 70° C. for one week, the absolute value of the rate of change in particle size or the absolute value of the rate of change in viscosity was 30% or more.

[0113] TIFF2025047711000011.tif124170

[0114] (Printed matter production) An inkjet printer with a plate heater (product name "MMP825H", manufactured by Mastermind), an inner surface corona-treated stretched polyethylene terephthalate film (PET film), and an inner surface corona-treated stretched polypropylene film (OPP film) were prepared. Then, using the inkjet printer, an image was recorded on the corona-treated surface of the film using water-based inks to obtain a printed matter. Specifically, the film was heated using a plate heater so that the surface temperature reached 50°C, and then each ink was applied to record an image, thereby obtaining a printed matter.

[0115] (Adhesion) Cellophane tape (product name "Cellotape (registered trademark)", manufactured by Nichiban Co., Ltd.) was pressed firmly onto the solid portion of the image that had been thoroughly dried, and then peeled off. The degree to which the image had peeled off was then visually observed, and the adhesion of the image to the film was evaluated according to the following evaluation criteria. The results are shown in Table 6. .circle-solid.: The image did not peel off at all. A: The image was slightly peeled off. Δ: The area of ​​the peeled image was smaller than the area of ​​the image that remained unpeeled. ×: The area of ​​the peeled image was larger than the area of ​​the image that remained unpeeled.

[0116] (Abrasion resistance) Using a Gakushin-type rub fastness tester (product name "RT-300", manufactured by Daiei Kagaku Co., Ltd.), the surface of the image on the obtained print was subjected to (1) dry rub with a white cloth weighing 500 g and reciprocating 100 times; (2) wet rub with a white cloth moistened with water weighing 200 g and reciprocating 100 times; and (3) ethanol rub with a white cloth moistened with 70% ethanol weighing 200 g and reciprocating 4 times. The state of the image after rubbing was visually observed, and rub resistance (dry rub resistance, wet rub resistance, and ethanol rub resistance) was evaluated according to the following evaluation criteria. The results are shown in Table 6. .circle-solid.: The image did not peel off at all. A: The image was slightly peeled off. Δ: The area of ​​the peeled image was smaller than the area of ​​the image that remained unpeeled. ×: The area of ​​the peeled image was larger than the area of ​​the image that remained unpeeled.

[0117] (Environmental friendliness) The environmental friendliness of the ink was evaluated based on whether or not a material that fixes carbon dioxide was used (if used: O, if not used: ×). The results are shown in Table 6.

[0118] TIFF2025047711000012.tif124170 [Industrial Applicability]

[0119] The water-based ink of the present invention is suitable for outdoor display printing and high-speed large-volume ink-jet printing, and is also useful as a water-based flexographic printing ink, a water-based paint, and an ink for water-based writing instruments.

Claims

1. The composition contains water, a water-soluble organic solvent, a pigment, a surfactant, a wax, a polyurethane resin, and an acrylic polymer, the polyurethane resin is a polyhydroxy polyurethane resin having a constituent unit derived from a 5-membered ring cyclic carbonate compound which is a reaction product of a diepoxy compound and carbon dioxide, and a constituent unit derived from a diamine compound; the acrylic polymer is an A-B block copolymer having A and B chains; The aqueous ink for ink-jet recording, wherein the content of the polyhydroxy polyurethane resin is 1 to 100 parts by mass based on 100 parts by mass of the AB block copolymer.

2. The polyhydroxy polyurethane resin has a weight average molecular weight of 10,000 to 100,000, a hydroxyl value of 150 to 250 mgKOH / g, and an acid value of 20 to 50 mgKOH / g; 2. The water-based ink according to claim 1, wherein the polyhydroxy polyurethane resin is contained in the form of particles having a number average particle diameter of 20 to 300 nm.

3. The aqueous ink according to claim 1 or 2, wherein the AB block copolymer satisfies the following requirements (1) to (3): (1) Contains 90% by mass or more of structural units derived from methacrylic acid and methacrylate monomers, The number average molecular weight is 10,000 to 60,000, the molecular weight distribution (weight average molecular weight / number average molecular weight) is 1.8 or less, and the acid value is 20 to 100 mgKOH / g. (2) The A chain has a structural unit (A) derived from at least one methacrylate monomer selected from the group consisting of methyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, ethyl methacrylate, isobornyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, behenyl methacrylate, and tetrahydrofurfuryl methacrylate; The content of the structural unit (A) in the A chain is 80 mass% or more, and the A chain has a glass transition temperature of 150°C or less, a number average molecular weight of 3,000 to 50,000, and a molecular weight distribution (weight average molecular weight / number average molecular weight) of 1.8 or less. (3) The B chain has a structural unit (B-1) derived from methacrylic acid, and a structural unit (B-2) derived from at least one methacrylate monomer selected from the group consisting of methyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, t-butylcyclohexyl methacrylate, ethyl methacrylate, isobornyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, behenyl methacrylate, and tetrahydrofurfuryl methacrylate, in the B chain, the content of the structural unit (B-2) is 80 mass% or more based on the total content of structural units other than the structural unit (B-1), The acid value of the B chain is 50 to 250 mgKOH / g and the number average molecular weight is 1,000 to 11,000, At least a portion of the carboxy groups in the B chain is neutralized with an alkali.

4. 4. The aqueous ink according to claim 3, wherein the alkali is at least one selected from the group consisting of ammonia, dimethylaminoethanol, 2-amino-1-propanol, sodium hydroxide, potassium hydroxide, lithium hydroxide, linear aliphatic amines having 6 to 22 carbon atoms, branched aliphatic amines having 6 to 22 carbon atoms, and unsaturated aliphatic amines having 6 to 22 carbon atoms.

5. 3. The aqueous ink according to claim 1, wherein the surfactant is at least one selected from the group consisting of silicone-based surfactants, acetylene glycol-based surfactants, and fluorine-based surfactants.

6. 3. The water-based ink according to claim 1, wherein the wax is a polyethylene wax.

7. the water-soluble organic solvent comprises propylene glycol and at least one selected from the group consisting of diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, and dipropylene glycol monomethyl ether; 3. The aqueous ink according to claim 1, wherein the content of the water-soluble organic solvent is 3 to 30% by mass based on the total mass of the ink.

Citation Information

Patent Citations

  • Water dispersion of polyhydroxyurethane resin, manufacturing method of water dispersion, and gas barrier film using water dispersion

    JP2016194029A

  • Binder resin used in aqueous inkjet ink

    JP2020105527A

  • Hydroxyurethane (meth)acrylate prepolymers for use in 3D printing

    JP2022517036A

  • Gravure printing ink composition, laminate and laminated product

    JP7317193B1

  • Modified colorants and inkjet ink compositions containing modified colorants

    JP2009515007A